Manejo de água e potassio por fertirrigação no maracujazeiro amarelo em alvorada do gurguéia, Piauí - Vasconcelos, Denise Vieira (2007)
This work aimed to study the effects of five layers of irrigation and five doses of potassium – applied through fertirrigation – on productivity and on quality of yellow passion fruits, in order to provide a proper crop management. The experiments were conducted on Embrapa Meio-Norte experimental field, in the municipality of Alvorada do Gurgueia, PI, Brazil, from March 2004 through April 2006. The experimental design consisted of randomized blocks with design in split-plots, with four replications. The treatments consisted of five doses of potassium (0,000; 0,225; 0,450; 0,650; 0,900 kg of K2O plant-1) and five irrigation layers (30; 60; 90; 120 and 150% of ECA). The plants were spaced by 2.5m x 4.0m. The results show that productivity and mean weight of fruits were significantly affected by irrigation layers, doses of potassium, as well as by the interaction term between the two factors; as for the number of fruits per hectare was significantly affected only by doses of potassium. Regarding the physical characteristics of the fruits, the longitudinal diameter and the juice production were significantly affected by number of layers, doses of potassium, and by the interaction term. The thickness of the rind was affected only by doses of potassium. As for the chemical characteristics of the fruits, only the level of total soluble solids was significantly affected by number of layers, doses, and by the interaction term; tritable total acidity (ATT) was affected only by doses of potassium; and pH was affected by none of the factors considered in this study. Among all treatment combinations, L4K4 yielded the highest fruit productivity, number, and mean weight. The levels of total soluble solids decreased with the increase layers applied, and the total acidity increased linearly with the increase of doses of potassium.